Corrosion Inhibition of Aluminium Using Exudate Gum from Pachylobus edulis in the Presence of Halide Ions in HCl. Issue 2 (2008) - Umoren, S. A.; Obot, I. B.; Ebenso, E. E.
Abstract : The anti-corrosive effect of Pachylobus edulis exudate gum in combination with halides ions (Cl –, Br – and I – ) for aluminium corrosion in HCl was studied at temperature range of 30-60 ° C using weight loss method. Results obtained showed that the naturally occurring exudate gum acts as an inhibitor for aluminium corrosion in acidic environment. Inhibition efficiency (%I) increases with increase in concentration of the exudate gum and synergistically increased to a considerable extent on the addition of the halide ions. The increase in inhibition efficiency (%I) and surface coverage (θ) in the presence of the halides was found to be in the order I – > Br – > Cl – which indicates that the radii as well as electronegativity of the halide ions play a significant role in the adsorption process. Pachylobus edulis exudate gum obeys Temkin adsorption isotherm. Phenomenon of physical adsorption is proposed from the values of kinetic and thermodynamic parameters obtained. The values of synergism parameter (S1) obtained for the halides are greater than unity suggesting that the enhanced inhibition efficiency of the P. edulis caused by the addition of the halide ions is only due to synergistic effect.